In vivo electrical stimulation of motor nerves - Szlavik, Bruce Robert (My University, 1999)
Stimulus waveform parameters and stimulation protocols are fundamental to the use of electrical stimulation in medical applications. This thesis presents new simulation and experimental procedures that for the first time can quantify the effects on nerve fiber recruitment patterns of variable stimulus waveform parameters, such as pulse width changes in the stimulation protocol with respect to electrode orientation. The study of the effect of variable electrical stimulus waveform parameters and stimulation protocols is important from the perspective of therapeutic and diagnostic medicine. Variations in the stimulus waveform such as stimulus pulse width have been shown to offer some promise in allowing for selective recruitment of nerve fibers and motor units based on nerve fiber diameter. The degree of selectivity achievable has not however been quantified under any stimulus electrode protocol. Standardization of electrodiagnostic techniques such as motor unit number estimation would also benefit from a quantified study of nerve fiber recruitment patterns under different stimulus pulse width conditions. Changes in the stimulus electrode orientation result in marked changes in the muscle response during conduction velocity tests. This phenomenon has not been investigated in any systematic fashion. In order to quantitatively study these effects, both theoretically and experimentally, a number of tools and techniques had to first be selected or developed that include: (i) a sufficiently realistic model of the myelinated nerve fiber and nerve trunk that, for the first time in electrical nerve excitation studies, incorporates information associated with anatomically consistent fiber diameter distributions; (ii) a more realistic model of the tissue surrounding this nerve trunk that includes electrical anisotropy; (iii) a field simulation technique used to determine the potential fields at the nerve fiber surfaces (with different diameters and electrode distances) resulting from stimulus pulses with different pulse widths; (iv) two novel sets of experiments, the first of which is used to stimulate a nerve trunk in vivo and from the resulting electrical response, determine the diameters of the nerve fibers that have "fired" under conditions of variable stimulus pulse width, the second of which is used to study the effect of electrode orientation on the stimulus response. The techniques outlined above facilitate a quantitative comparison between experimental and simulation results for the stimulus current pulse width studies as opposed to purely qualitative comparisons that have been reported in the literature. A novel instrument design prototype is presented based on the electrode orientation experiment, that can be used to standardize stimulus electrode orientation for multiple EMG (Electromyography) tests performed on a single subject at different times.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering